نحو منهجية للتعامل مع الأحاديث المنتقدة في الصحيحين حديث "لولا حواء لم تخن أنثى زوجها نموذجاً": "Towards a Methodology of Dealing with Critiqued Hadiths in the Two Sahihs" - البنا نماء محمد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2012)
هذا البحث مثال على التفاوت والاختلاف في منهجية التعامل مع السنة النبوية بشكل عام، وأحاديث الصحيحين بشكل خاص. هناك مدرستان في ذلك؛ إحداهما ترى ضرورة قبول الأحاديث الموجودة فيهما وعدم السماح بمناقشتها أو فهمها فهماً جديداً أو ردّها؛ وأخرى ترى ضرورة المراجعة الشاملة للسنة، وردّ ما قد يبدو متعارضاً مع العقل، حتى وإن ورد في الصحيحين واستجمع شروط الصحة، وتطرح الباحثة في هذا البحث منهجية لمدرسة ثالثة تقول: إن الحديث إذا استجمع شروط الصحة، وهو ممكن عقلاً، إلا أن فهمه مُشكِل، فلا مانع من التوقف فيه، دون ردّه ودون دفاع عنه، مع التزام ثوابت أخرى لهذه المنهجية أوردتها الباحثة في خاتمة بحثها. This study is an example of the differences existing among scholars in the methodology of dealing with the sunnah of prophet Muhammad peace be upon him, and in Sahih Bukhari and Sahih Muslim in particular. There are two schools in this regard, the first adopts the idea of accepting hadiths of the two sahihs, understanding them as they are, and not dismissing them. The second school allows a comprehensive revision of the sunnah, and rejects what seems in conflict with reason, even if the hadith appears in one of the two sahihs. The author presents a third school which says: if the hadith has all the conditions of being sahih and is in line with reason, but it presents a problem in its understanding, there will be no problem to question the hadith without rejecting it all together.